50 años Departamento de Biología de la Universidad Pedagógica Nacional (Colombia) - Chona Duarte, Guillermo; Pacheco Calderón, Diana; Romero Acuña, Diana Carolina; Sierra Fandiño, Luz Maritza (Bio-grafía, 2019)